2020
DOI: 10.1080/10454446.2020.1720885
|View full text |Cite
|
Sign up to set email alerts
|

Chinese consumers’ perceptions of immune health and immune-boosting remedies including functional foods

Abstract: To facilitate the successful design of functional foods designed to boost immunity and to guide the successful promotion of such products, to Chinese consumers, fundamental knowledge is required on how consumers perceive the concept of immunity, the steps they take to improve their immunity and what their general attitudes are toward new functional food products. To explore these issues, focus groups (n = 4) and inhome semi-structured interviews (n = 12) were conducted in Shanghai. Immunity was understood to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…For example, health-conscious individuals may have prioritised the health benefits of the low-salt alternative, even if other options are more popular. Thus, it corroborates earlier studies that Chinese consumers, particularly those in urban areas are becoming increasingly aware of the benefits of healthier eating and are now placing importance on healthy diets (Cong et al ., 2020; Jiang et al. , 2023).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, health-conscious individuals may have prioritised the health benefits of the low-salt alternative, even if other options are more popular. Thus, it corroborates earlier studies that Chinese consumers, particularly those in urban areas are becoming increasingly aware of the benefits of healthier eating and are now placing importance on healthy diets (Cong et al ., 2020; Jiang et al. , 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, the findings from this paper would inform strategies for promoting healthy eating habits at a population level and inform the design of effective interventions on public health strategy for healthy food. Considering the number of Chinese consumers, particularly those in urban areas that are aware of the benefits of healthier eating and place importance on health are gradually increasing (see Cong et al, 2020;Jiang et al, 2023), the paper would provide insights into avenues to influence consumption of healthy foods. Further, the empirical evidence from the paper could assist food manufacturers and businesses in harnessing social influences to develop effective marketing and pricing strategies to promote healthier and more sustainable food choices.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of cereals, Bogue and Yu (2016) found that perceptions of health were associated with various product-level attributes such whether cereals helped with weight control, cholesterol, digestion and a had low glycaemic index, and whether they contained probiotics, soluble fibre, vitamins and minerals. Forbes et al (2016) showed that sugar, fat, additives, calories and sodium content were among the most important factors influencing the perceived health of snack food products, while Cong et al (2019, 2020) found that perceptions about the health of functional foods were associated with specific benefits such as lung moistening, micronutrients, and cough relief as well as more general benefits such as strengthening immune health.…”
Section: Perceptions About the Health Of Foodsmentioning
confidence: 99%
“…Despite the economic pressures of the pandemic on consumers, a Romanian study demonstrated an increased consumption of organic food amongst those with some organic food consumption already, but not a significant adoption of organic food consumption from those indifferent prior to the pandemic [25]. Other studies have seen an increased consumption of organic food [26][27][28][29], and entertaining heterodox beliefs on COVID-19 was a significant predictor of support for organic food [30].…”
Section: Introduction: a Loss Of Trustmentioning
confidence: 99%